A Multi‐Doped Electrocatalyst for Efficient Hydrazine Oxidation. Issue 52 (27th November 2018) - Ojha, Kasinath; Farber, Eliyahu M.; Burshtein, Tomer Y.; Eisenberg, David
Abstract: We report an efficient electrocatalyst for the oxidation of hydrazine, a promising fuel for fuel cells and an important analyte for health and environmental monitoring. To design this material, we emulated natural nitrogen‐cycle enzymes, focusing on designing a cooperative, multi‐doped active site. The catalytic oxidation occurs on Fe2 MoC nanoparticles and on edge‐positioned nitrogen dopants, all well‐dispersed on a hierarchically porous, graphitic carbon matrix that provides active site exposure to mass‐transfer and charge flow. The new catalyst is the first carbide with HzOR activity. It operates at the most negative onset potentials reported for carbon‐based HzOR catalysts at pH 14 (0.28 V vs. RHE), and has good‐to‐excellent activity at pH values down to 0. It shows high faradaic efficiency for oxidation to N2 (3.6 e − /N2 H4 ), and is perfectly stable for at least 2000 cycles. Abstract : Cooperative active sites in nitrogen‐cycle enzymes inspired the design of a multi‐doped, efficient electrocatalyst for hydrazine oxidation. The catalytic oxidation occurs on Fe2 MoC nanoparticles and on edge‐positioned nitrogen dopants, all well‐dispersed on a hierarchically porous, graphitic carbon matrix.